2012
DOI: 10.1155/2012/656025
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Palm Vitamin E on Bone-Formation-Related Gene Expression in Nicotine-Treated Rats

Abstract: The study determines the effects of palm vitamin E on the gene expression of bone-formation-related genes in nicotine-treated rats. Male rats were divided into three groups: normal saline olive oil (NSO), nicotine olive oil (NO), and nicotine palm vitamin E (NE). The treatment was carried out in 2 phases. During the first 2 months, the NSO group received normal saline while the NO and NE groups received nicotine 7 mg/kg, 6 days a week, intraperitoneally. The following 2 months, normal saline and nicotine admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 20 publications
2
15
1
2
Order By: Relevance
“…Evidence shows that vitamin E can reverse nicotineinduced toxic effects on bone biochemical markers and osteogenic gene expression [5,6]. These findings were in line with our results, which showed that the negative effects of 5 mM nicotine on ALP/BSP/OC expression significantly decreased in the presence of 5 mM vitamin E to the normal level.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Evidence shows that vitamin E can reverse nicotineinduced toxic effects on bone biochemical markers and osteogenic gene expression [5,6]. These findings were in line with our results, which showed that the negative effects of 5 mM nicotine on ALP/BSP/OC expression significantly decreased in the presence of 5 mM vitamin E to the normal level.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, animal experiments showed that oxidative stress induced by nicotine affected bone metabolism by down-regulating the expression of osteogenic genes [14]. Vitamin E possesses antioxidant properties, and it was shown that it up-regulated osteogenic gene expression in nicotine-treated rats [6] and improved structural, dynamic and cellular histomorphometric parameters of bone [4,5,40,41].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…T3 may also affect the formation and activities of bone cells at gene levels. Utilizing nicotine-induced osteoporosis rat model, Abukhadir et al (2012) reported that PVE increased gene expression related to bone formation such as BMP-2, a growth factors known to induce bone and cartilage formation, as well as Runt-related transcription factor 2 (Runx-2) and osterix (OSX), which play key roles in osteoblast differentiation [165]. In the testosterone deficiency model, annatto T3 enhanced the expression of gene related to bone formation and osteoblast activity, such as alkaline phosphatase (ALP), β-catenin, and collagen type I alpha 1 (COL1α1) [147].…”
Section: Effects Of Tocotrienol On Osteoporosismentioning
confidence: 99%